Biomechanical comparison of multiple zero-profile systems in anterior cervical discectomy and fusion: a finite element analysis - Xiong-han Lian; Wen-jia Sun; Huo-huo Xue; Yu-fan Chen; Zhi-feng Zeng; Jing-lai Xue (Journal of Orthopaedic Surgery and Research)
Abstract Background Anterior cervical discectomy and fusion (ACDF) with zero-profile (ZP) implant is commonly used for cervical degenerative diseases, but subsidence remains a concern, particularly in osteoporosis. The two-screw ZP (TSZP), four-screw ZP (FSZP), and ROI-C implants are frequently applied, yet the biomechanical performance across varying bone qualities remains unclear. Methods A finite element (FE) model of the cervical spine (C3-C7) was constructed with TSZP, FSZP, and ROI-C implants at C4/C5 to simulate normal and osteoporotic conditions. A 73.6 N load and 1 Nm torque were applied at C3 to simulate flexion, extension, lateral bending, and axial rotation, followed by biomechanical analysis. Results The FSZP implant exhibited the smallest ranges of motion, followed by ROI-C, with the largest in TSZP. ROI-C showed the lowest peak implant system stresses, while TSZP had the highest on the anchoring device and FSZP on the cage. The TSZP implant had the highest cortical endplate stresses, whereas FSZP had the lowest in normal and ROI-C in osteoporosis. No significant differences were observed in adjacent intervertebral disc pressures. All parameters increased in osteoporosis, except cortical endplate stresses. Conclusion The FSZP implant provided superior stability, while ROI-C exhibited a lower risk of implant-related complications. The TSZP implant was more prone to subsidence, which may be mitigated by optimizing stress distribution and enhancing damage prevention. Biomechanical performance was poorer under osteoporotic conditions, highlighting the need for careful surgical planning.